Does grade level or gender matter? Assessing secondary school students’ scientific literacy in the knowledge dimension - Soraya Firdausi; Hamdan Dwi Rizqi; Firdha Yusmar; Rizka Elan Fadilah; Sri Rejeki Dwi Astuti (University of Muhammadiyah Malang, 2025)
Scientific literacy is recognized as a critical and essential 21st-century competency, particularly in response to global challenges that demand individuals to think critically, solve problems, and make evidence-based decisions. This study investigates the scientific literacy of secondary school students, focusing on the knowledge dimension, which includes understanding scientific concepts, processes, and the applications of science in everyday life. Additionally, the study investigates potential differences in scientific literacy based on gender and grade level. The research involved 150 secondary school students in Situbondo, selected through random sampling. The instrument used was a scientific literacy test comprising 33 items that were validated and tested for reliability before implementation. Due to non-normal data distribution, the Mann-Whitney U and Kruskal-Wallis tests were used for gender-based and grade-based analysis. The results indicated the students' scientific literacy in the knowledge dimension was high. Moreover, the analysis showed no significant differences in knowledge-based scientific literacy scores across gender and grade levels. These findings are expected to provide a comprehensive understanding of students' scientific literacy and to inform the development of more effective and contextually relevant science learning strategies.